The Mediating Effect of Peer Communication between Social Withdrawal and Life Satisfaction of College Students - Soo-Koung Jun (National Research Mordova State University, 2019)
Introduction. In this study, an examination as to whether social withdrawal on the part of college students has an effect on satisfaction with college life is presented along with an analysis of the possible mediating effect of peer communication on social withdrawal and dissatisfac tion with college life. Material and Methods. A total of 1,220 college students were analysed using the 7th year data of the Korea Child and Youth Panel Survey conducted by Korea Youth Policy Institute in 2016. Analysis using SPSS 23 and AMOS 23 software programs was carried out, along with t-test, ANOVA and structural equation analysis. Results. A significant variation in satisfaction with college life according to demographic factors was noted. It was also found that social withdrawal has a direct impact on satisfaction with college life: the higher the degree of social withdrawal, the higher the satisfaction with college life. Moreover, social withdrawal increases satisfaction with college life as a function of peer communication. In other words, peer communication indirectly affects both social withdrawal and satisfaction with college life . Discussion and Conclusion. Based on the results of this study, practical suggestions are proposed for improving the life satisfaction of college students. Programs for improving peer communication and increasing social interaction should be developed for college students.